2010
DOI: 10.2215/cjn.08241109
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-23 in Early Chronic Kidney Disease

Abstract: Conclusions: Our data are in favor of the new paradigm for the pathogenesis of secondary hyperparathyroidism according to which a reduced phosphate excretion capacity is the principal abnormality that initiates secondary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 57 publications
6
90
1
3
Order By: Relevance
“…FGF23 controls phosphate and vitamin D metabolism, and it is a primary regulator of renal phosphate excretion (10,26). It is inversely associated with GFR (9); this mechanism is fundamental to maintain serum phosphate at constant levels as renal function worsens.…”
Section: Discussionmentioning
confidence: 99%
“…FGF23 controls phosphate and vitamin D metabolism, and it is a primary regulator of renal phosphate excretion (10,26). It is inversely associated with GFR (9); this mechanism is fundamental to maintain serum phosphate at constant levels as renal function worsens.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with cardiac failure [16,17], acute renal failure [18], chronic kidney disease [7,17,19], diabetic nephropathy [20] and hepatic failure [21], plasma FGF23 concentrations are high and associated with accelerated disease progression, morbidity and/or mortality. Mechanisms up-regulating FGF23 in those disorders are still ill-defined.…”
Section: Introductionmentioning
confidence: 99%
“…Early increases in FGF23 secretion play a key role in the initiation and progression of disordered bone and mineral metabolism in CKD (2,3). Studies have also shown that increased FGF23 is independently linked with cardiovascular disease events and mortality in individuals across a broad range of kidney function (4)(5)(6)(7)(8), establishing excess FGF23 as a novel risk factor for adverse clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%